1984
DOI: 10.1016/0167-2738(84)90030-4
|View full text |Cite
|
Sign up to set email alerts
|

Ionic conductivity in tysonite-type solid solutions La1−xBaxF3−x

Abstract: The ionic conductivity of single crystals of tysonite-type solid solutions Lal_xBaxFa_x(O • x • 0.095) has been studied parallel and perpendicular to the crystallographic c axis in the temperature range 293-1300 K. Three regions can be discerned in the compositional dependence of the ionic conductivity: (i) the "pure" crystal, in which at room temperature no exchange occurs between different types of anion sites in the tysonite structure; (ii) an intermediate region (0 < x < 7 X 10 -2) which reveals changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
2

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 31 publications
(61 reference statements)
5
56
0
2
Order By: Relevance
“…The electronic conductivities of these materials reveal no anisotropy. The compositions of the La I -x BaxF3-x samples reported here, have been determined by neutron activation analysis [14], and are included in table 1 The unblocked specific ionic current of these materials, has been reported in a previous study [14]. These data reveal that the contribution of the electronic current to the total conductivity is negligible.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The electronic conductivities of these materials reveal no anisotropy. The compositions of the La I -x BaxF3-x samples reported here, have been determined by neutron activation analysis [14], and are included in table 1 The unblocked specific ionic current of these materials, has been reported in a previous study [14]. These data reveal that the contribution of the electronic current to the total conductivity is negligible.…”
Section: Resultsmentioning
confidence: 64%
“…We have determined only ionic defect mobilities (see ref. [14]) so we cannot present a more specific value for the constraint. However, in the limiting case, [h'] = [VF], one would expect a = 2, ref.…”
Section: Disc!l~ionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorine ions labelled F 1 in literature [18] account for most of the Cerium Fluoride conductivity and hence their mobility might help repair defects. There is a vast literature on this and in particular on doping [19] with Barium and Strontium, which have been observed to increase the conductivity even further [20]. The composition which maximizes conductivity might maximize radiation hardness as well, as hypothesised in [21], but establishing this would require a dedicated R&D. It should also be noticed that the Cerium Fluoride conductivity increases by a factor 4 between 20 o C and 50 o C temperature [21], while its Light Output remains unaffected.…”
Section: Cerium Fluoridementioning
confidence: 99%
“…It has been observed that fast fluorine motion within the F A sublattice leads to a narrowing of the corresponding resonance line, while the F B line stays broad until it collapses with the faster one. It is worthwhile to mention that also other experimental techniques providing directly some macroscopic physical quantities, like fluorine conductivity [20,21] have been applied to investigate the fluorine dynamics.…”
Section: Mechanisms Of Fluorine Spin Relaxation In Laf 3 Crystalsmentioning
confidence: 99%